Changes in malondialdehyde concentrations and glutathione peroxidase activity in purebred Arabian mares with endometritis - Yaralioglu-Gurgoze, S; Cetin, H; Cen, O; Yilmaz, S; Atli, MO (Elsevier Sci Ltd, 2005)
Endometritis is an important factor in infertility. Free radicals play an important role in endometritis and we have investigated their possible role and scavenging systems in endometritis in purebred Arabian mares. The plasma concentration of majondialde-hyde (MDA) and erythrocyte glutathione peroxidase (GPx) activity were compared in healthy mares and in mares with endometritis. The level of MDA was significantly increased while GPx activity was decreased in the mares with endometritis. Our findings support the notion that GPx is consumed by increased lipid peroxidation in purebred Arabian mares affected with endometritis. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: glutathione peroxidase; malondialdehyde; endometritis; Arabian mares